Catalan maps and Jewish books the intellectual profile of Elisha ben Abraham Cresques (1325-1387) - Kogman-Appel, Katrin 1958- (Brepols, 2020)
This books describes the life of Elisa ben Abraham Cresques, known to many as the author of the Catalan Atlas, and focuses on the Jewish aspects of his fascinating career, his professional profile, and his scholarship.00This book presents a small chapter in the intellectual history of the Jews of Majorca. Its key figure is Elisha ben Abraham Bevenisti Cresques (1325-1387) a cartographer in the service of King Peter IV of Aragon and a scribe and illuminator of Hebrew books. Elisha Cresques? career evolves at a point in time when some of the most fascinating threads of methodological interests relevant to intellectual history meet. He emerges as a hub, so to speak, where mapmaking converged with scribal work, miniature painting with scientific knowledge, and the culture of a minority with that of the majority. How he was able to negotiate his patron?s expectations and his own cultural identity and frame them within the political, cultural, and religious discourses of his time is the subject of this book.
Enthält bibliographische Angaben und Index. - Includes bibliographical references and index
Keywords: Cresques, Abraham -- 1325-1387; Buchmalerei; Kartografie; Judaika